(untitled) (Jóvenes en la Ciencia, 2026)
Soil mechanics is a fundamental area of ​​civil engineering, responsible for understanding the behavior of soil under loads and physical changes. This article presents, in an accessible way, the main laboratory tests used to analyze soils: compaction, unconfined compression, triaxial, etc. Their fundamentals, essential procedures, and practical relevance are described. Based on the analysis of these tests, the typical results obtained and their importance for geotechnical design are discussed. Finally, the role of university laboratories in the training of engineers and in improving safety is considered.